Perancangan Fasilitas Dan Landscape Coffee Serenity - Ginting, Arca Iswari Br; Sianipar, Christina Indriani (Politeknik Pariwisata Medan, 2024)
Cafes are now a trend for many people and can be found anywhere with a variety of concepts offered to attract interest in visiting. Cafes usually have an attractive and unique interior design, thus creating a comfortable atmosphere for customers. Some cafes have a particular theme or concept, such as a cafe with a vintage concept or a cafe with a nature concept, thus creating a different experience for customers. In general, a cafe or cafeteria is a suitable place for customers who want to enjoy food, drinks and a relaxed and informal atmosphere. This study aims to design facilities and café serenity landscapes. This study used a qualitative method which was obtained through direct visits to Café Serenity. The data collection method is by conducting interviews with the Owner Café Serenity. The results of the discussion from this study are that space planning applies a lot of modern street art styles. The use of color in the cafe does not use a lot of bright colors. The color used is gray. The dominant rural nuance and the combination of streets gives a natural and modern impression. Serenity Café Design Design which is located on Jl. Tiung Raya, State Housing Corporation, Medan City, North Sumatra. This location was chosen by the author because it has a strategic location, especially in urban areas. The Owner Cafe aims to build the cafe, so that visitors can hang out comfortably and provide an industrial, aesthetic concept atmosphere, but still far from the hustle and bustle of the city. Industrial style is an applied art in which the aesthetics and usability (ease of using an item) of an item are perfected.